Augmented Reality-Based Design of Shoes for Arthritis - Hashim, Nabil Fikri; Koh Ching Theng (Research Progress in Mechanical and Manufacturing Engineering, 2022)
Rheumatoid arthritis is a common disease found in the forefoot part. Most rheumatoid arthritis patients suffered in deformity that would change the foot shape and dimension. The deformity results problem of poor-fitting shoes that worsen the patient mobility condition. The objective of this research is to identify the foot dimension and geometry of arthritis patient using an Augmented Reality(AR) Software and design a 3-dimensional shoe model based on the design for arthritis using the dimension and geometry obtain from the AR application. The measurement was done using 3D Avatar Feet Mobile Application to measure the foot dimension of an arthritis patient. The shoes was then design using SolidWorks software with reference to the existing design from Propet Cush’N Foot. The 3D Avatar Feet generated four dimension which are Foot Length, Ball Width, Ball girth and Instep Girth. The designed features, which are produced from the design of the 3D shoe model using the dimension and geometry from the 3D Avatar Feet Mobile Application, include wide toe box, extra depth, wide heel and deep toe box. The results from the AR Software are acceptable as the percentage error calculated are less than 5The constructed shoe model has better fitting to the distorted feet of arthritis patients as compared to the existing products.